Percepción de riesgo y práctica sobre medidas preventivas de dengue en pobladores del asentamiento humano 13 de Noviembre Iquitos 2021 - Soria Arévalo, Yurika Zaidita (2023)
The research problema was the following: ¿Is there a relationship between the perception of risk and the practice on preventive measures of Dengue in residents from 18 to 70 years of age of both sexes of the Human Settlement November 13 Iquitos, 2021? The objective was to determine the relationship between the perception of risk and the practice on preventive measures of Dengue in residents from 18 to 70 years of age of both sexes of the Human Settlement November 13 Iquitos, 2021. The study was Quantitative with non – experimental design, correlational, the population was 161 residents. The techniques that were used were the interview, observation and home visit; The instruments were the Dengue Risk Perception Scale with 94.0% validity and 92.6% reliability, and the Practice Checklist on Dengue preventive measures with 96.3% validity and 93 reliability. 5%. The study determined high risk perception of Dengue 52.2% and low risk perception 47.8%. In practices on preventive measures of Dengue, 62.1% had incorrect practices, while 37.9% correct practices. By applying the non-parametric Chi-Square statistical test, significant statistical results were obtained X = 24.354; p = 0.000; α < 0.05; df = 1; 95% confidence level. The study concluded that there is a significant statistical relationship between the perception of risk and practice on preventive measures of Dengue in residents from 18 to 70 years of age of the Human Settlement November 13 Iquitos.